Root System Scale Models Significantly Overestimate Root Water Uptake at Drying Soil Conditions - Khare, Deepanshu; Selzner, Tobias; Leitner, Daniel; Vanderborght, Jan; Vereecken, Harry; Schnepf, Andrea (Frontiers in Plant Science, 2022)
Soil hydraulic conductivity (ksoil) drops significantly in dry soils, resulting in steep soil water potential gradients (ψs) near plant roots during water uptake. Coarse soil grid resolutions in root system scale (RSS) models of root water uptake (RWU) generally do not spatially resolve this gradient in drying soils which can lead to a large overestimation of RWU. To quantify this, we consider a benchmark scenario of RWU from drying soil for which a numerical reference solution is available. We analyze this problem using a finite volume scheme and investigate the impact of grid size on the RSS model results. At dry conditions, the cumulative RWU was overestimated by up to 300% for the coarsest soil grid of 4.0cm and by 30% for the finest soil grid of 0.2cm, while the computational demand increased from 19 seconds to 21 hours. As an accurate and computationally efficient alternative to the RSS model, we implemented a continuum multiscale model where we keep a coarse grid resolution for the bulk soil, but in addition, we solve a 1-dimensional radially symmetric soil model at rhizosphere scale around individual root segments. The models at the two scales are coupled in a mass conservative way. The multiscale model compares best to the reference solution (−20%) at much lower computational costs of 4 minutes. Our results demonstrate the need to shift to improved RWU models when simulating dry soil conditions and highlight that results for dry conditions obtained with RSS models of RWU should be interpreted with caution.